Intravitreal Anti-VEGF Drugs and Signals of Dementia and Parkinson-Like Events: Analysis of the VigiBase Database of Spontaneous Reports - Janet Sultana; Giulia Scondotto; Paola Maria Cutroneo; Francesca Morgante; Francesca Morgante; Gianluca Trifirò; Gianluca Trifirò; Gianluca Trifirò (Frontiers Media S.A., 2020)
IntroductionSince vascular endothelial growth factor (VEGF) regulates several aspects of the central nervous system, particularly in dopaminergic neurons, VEGF inhibitors may be linked to Parkinson-like events and dementia, or variants of these diseases. Two recent case reports have found a potential link between intravitreal anti-VEGF use and Parkinson's disease (PD) and dementia.AimTo evaluate disproportionality in a large spontaneous reporting database concerning intravitreal anti-VEGF drugs and PD or dementia, and related conditions.MethodsUsing VigiBase, individual case safety reports (ICSRs) attributed to intravitreal ranibizumab, aflibercept, pegaptanib, and bevacizumab were identified from 2010 to 2016. Within Standardised Narrow Medical Dictionary for Regulatory Activities (MedDRA®) Queries (SMQs) for "Parkinson-like events" and "Dementia," suspected events were identified using preferred terms (PTs). The Proportional Reporting Ratio (PRR) was estimated with the lower 95% confidence intervals (CIs) for all drug-event pairs with ≥3 suspected events. The vigiGrade completeness score was reported for the ICSRs. The analyses were repeated, including only persons aged 65 and over.ResultsOut of 18.9 million ICSRs, 7,945 (0.004%) concerned intravitreal anti-VEGF drugs. Of these, 27 (0.34%) were identified concerning the SMQs "Dementia" (N = 17, 62.96%) and "Parkinson-like events" (N = 10, 37.94%) in persons of all ages. Among persons age 65 and over, 4,758 (59.88% of relevant ICSRs) ICSRs were identified for anti-VEGF drugs. When restricting disproportionality analysis to persons aged 65 and over, no disproportionality was seen for any of the drug-event pairs at the level of SMQ. However, on analysing disproportionality by PT, a potential signal emerged for intravitreal ranibizumab and Parkinson's disease [N = 6 ICSRs; PRR: 3.05 (95% CI: 1.36-6.81)]. In general, the vigiGrade completeness score was low for all the ICSRs of interest, as no ICSR had a score >0.8.ConclusionPresent findings suggest a potential signal for Parkinson's disease related to intravitreal ranibizumab. This is supported by several biologically plausible mechanisms but requires confirmation through pharmacoepidemiological studies, especially because of the low number of cases.